Industrial control electronics : - Bartelt, Terry (Thomson Delmar Learning, 2006)
This new edition continues to provide state-of-the-art coverage of the entire spectrum of industrial control, from servomechanisms to instrumentation. Material on the components, circuits, instruments, and control techniques used in today's industrial automated systems has been fully updated to include new information on thyristors and sensor interfacing and updated information on AC variable speed drives. Following an overview of an industrial control loop, readers may delve into individual sections that explore each element of the loop in detail. This logical format offers the flexibility needed to use the book effectively in a variety of courses, from electric motors to servomechanisms, programmable controllers, and more!